EKSISTENSI PEREMPUAN DALAM NOVEL KITAB OMONG KOSONG KARYA SENO GUMIRA AJIDARMA : KAJIAN FEMINISME EKSISTENSIALIS SIMONE DE BEAUVOIR - Purnami, Kristanti; Pramono, Dedi (MIMESIS, 2021)
The background of this research is the significance of women’s awareness in the construction of women’s existence including the existence of women characters in a novel. This research is aimed to discover the types of women’s marginalization in Seno Gumira Ajidarma’s Kitab Omong Kosongand to find the model of women’s resistance as the manifestation of existence. The reference theory of women’s existance is a feminist theory proposed by France feminist, Simone de Beauvoir. In this research, Ajidarma’s Kitab Omong Kosongis used as the data source, while the Beauvoir’s theory is adopted as the object. This is a descriptive-qualitative research using documentation method. In analyzing the data, the techniques used were reading and writing notes, which, then the results of analyzing process were presented descriptively. Those results show that the type of women’s marginalization appeared in Ajidarma’s novel is in the form of women’s position considered low and subordinate, which, then, issues numbers of different forms of violence against women. Then, the resistances of women characters found as the forms of women’s existence in this research are women’s struggle for intellectuality, women’s refusal to be the victim of society, and women’s decision for their own fate.